Gender-based violence in confined women during the SARS-CoV-2 pandemic - Torres-Velasco, Diana Patricia; Salas-Cortez, Beatriz; Martínez-Basilio, Dulce Giseli; Mejía-Cervantes, Rosa; Vásquez-Martínez, Josué; Zacarías-Martínez, Monserrat (Horizonte Sanitario, 2022)
Objective: To identify the presence of gender-based violence in women confined due to the Covid-19 pandemic in the Oaxaca Coast Region. Materials and methods: Quantitative, descriptive, correlational and cross-sectional research in 50 women over 18 years of age who remained at least 1 month in confinement due to the Covid-19 pandemic, who applied a questionnaire using the Intimate Partner Violence Severity Index, respecting the pertinent ethical recommendations of the General Health Law on Health Research. The data were processed in the SPSS version 21 statistical program and descriptive statistics and Pearson´s correlation coefficient were used. Results: A prevalence of psychological violence was found to be 90%. 72% of the women reported physical violence and 64% were victims of sexual violence. A positive correlation was observed between age and physical violence (r= 0.405, p= 0.004), psychological violence (r= 0.416, p= 0.003) and sexual violence (r= 0.527, p= 0.000); a negative correlation was observed in the variables schooling and physical violence (r= -0.538, p= 0.000), psychological violence (r= -0.488, p= 0.000), sexual violence (r= -0.411, p= 0.003). Conclusions: Gender-based violence is an issue that has taken great relevance in recent years, and that currently continues to be of concern. Despite the fact that information has been disseminated, violence continues to exist within mexican homes. In the Oaxaca Coast during the confinement by Covid-19, gender-based violence has been highly prevalent, which is why it is necessary to implement measures to prevent and treat gender-based violence. Keywords: Gender-based violence; Confinement; Women.